THE ROLE OF THE LINGUOCULTURAL COMPONENT IN THE PROCESS OF INTERCULTURAL COMMUNICATION - Inna Yu. Pidhorodetska (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
Problems of intercultural communication have been of the research interests for several decades. The term “intercultural communication” (in the narrow sense) appeared in scientific works in the seventies of the 20th century. At that time, a scientific direction was formed in the study of communicative failures and their consequences in situations of intercultural communication. Subsequently, the concept of intercultural communication extended to such areas as translation theory, foreign language teaching, comparative culturology, and others. But even so far, the study of intercultural communication focuses on the behavior of people who encounter language and cultural differences during a communicative act and the consequences of these differences. The works by F. Batsevych, P. Donets, A. Levytskyi, V. Manakin, M. Berhelson, D. Hudkov, V. Sado- Donets, A. Levytskyi, V. Manakin, M. Berhelson, D. Hudkov, V. Sadochin, O. Leontovich, S. Ter-Minasova and other Ukrainian and foreign scientists are devoted to the theoret- ts are devoted to the theoretical and empirical issues of intercultural communication. The aim of the study is to find out the influence of linguistic and cultural factors on the process of intercultural communication. Intercultural communication participants are carriers of different cultures. The closer the cultures, the easier it is to communicate between their representatives. The remoteness of cultures can be an obstacle for understanding. Therefore, even lexical units to determine well-known concepts require additional interpretation and background cultural knowledge. For those who master Foreign language it should become, a tool for verbal communication, as well as a means of immersion into a foreign-language picture of the world, a foreign-speaking cultural environment, where their laws and rules prevail (and not only grammatical ones). Thus, the use of certain grammatical forms of pronouns is one of the decisive indicators of communication status. The formality / informality of communication in the Ukrainian language primarily depends on the use of language constructions with the personal pronouns ти/ви. Pronouns to designate a polite appeal are also in other European languages. But in English there is no form of personal pronoun with the named function. The markers of the official English-language communication are etiquette forms of appeal, greetings, farewells. In the English-language official communication, traditional etiquette formulas of courtesy are used correspondingly to literary norms, and in the informal one – they use speech constructions inherent in colloquial style. It allows to distinguish between formal and informal communication even when a specific form of a personal pronoun is absent. Learning a foreign language, one must pay attention not only to the language, but also to cultural differences, to get acquainted with the rules of communicative behavior in the foreign linguocultural space. In order to achieve success in intercultural communication, the linguistic and cultural components become of great importance. Knowledge of the language and cultural codes in their interaction allows to prevent communicative problems and conflicts, to realize the vision diversity of the world through the prism of other languages and cultures.